Changing patterns of Oral & Maxillofacial injuries before and during COVID-19 pandemic: A retrospective study - Ramakrishna Shenoi; Jignesh Rajguru; Simran Sangani; Vrinda Kolte; Ishani Bhave; Jui Karmarkar; Nimish Situt; Mayank Gajbhiye (Elsevier, 2022)
Introduction: Oral and maxillofacial injuries can be defined as injuries involving soft and hard tissue structures of the facial region and oral cavity, including the teeth and vital structures of the head and neck area as a result of trauma. The maxillofacial injuries are multifactorial and vary from one country to another and even from region to region. Despite, societal restrictions imposed by the government in the form of lockdowns and curfews, patients still experienced trauma and required significant healthcare services for management. Methods: Patients of either gender reporting to the emergency department of Lata Mangeshkar Hospital with maxillofacial injuries, attended by residents of OMFS from October 2019 to August 2020 were included in the retrospective study. The demographic data about age, gender and status pertaining to under the influence of alcohol was recorded. The aim of this retrospective study was to evaluate the changing patterns of the maxillofacial injuries during the Covid-19 pandemic. Results: In the present study, the road traffic accidents were 72.50% pre-lockdown which reduced to 47.37% during the alcohol ban and nationwide lockdown and gradually increased to 63.83% post-lockdown. The second most common cause of maxillofacial injury was falls which showed a significant increase from 22.50% before the lockdown to 31.58% during the lockdown and decreased to 26.6% after lockdown during the pandemic. There was an increase in the number of assaults from 2.50% pre-lockdown to 15.79% during the lockdown and again a decrease to 6.38% post-lockdown. Discussion: Our study demonstrates the impact of nationwide lockdown in the month of April and May 2020, may have an association with the significant statistical decrease in the monthly average number of trauma admissions. There was a significant decrease in the number of road traffic collisions and falls during the "lockdown period". Conclusion: The etiology and pattern of maxillofacial injuries reflect the trauma pattern within the community. We need more coordinated strategies of action to minimize maxillofacial injuries and its implication on physical and psychological wellbeing of patients.